A review of the mosquito species (Diptera: Culicidae) of Bangladesh - Irish, Seth R. (Parasit Vectors, 2016)
BACKGROUND: Diseases caused by mosquito-borne pathogens remain an important source of morbidity and mortality in Bangladesh. To better control the vectors that transmit the agents of disease, and hence the diseases they cause, and to appreciate the diversity of the family Culicidae, it is important to have an up-to-date list of the species present in the country. Original records were collected from a literature review to compile a list of the species recorded in Bangladesh. RESULTS: Records for 123 species were collected, although some species had only a single record. This is an increase of ten species over the most recent complete list, compiled nearly 30 years ago. Collection records of three additional species are included here: Anopheles pseudowillmori, Armigeres malayi and Mimomyia luzonensis. CONCLUSIONS: While this work constitutes the most complete list of mosquito species collected in Bangladesh, further work is needed to refine this list and understand the distributions of those species within the country. Improved morphological and molecular methods of identification will allow the refinement of this list in years to come.